PERANCANGAN APLIKASI INFORMASI BATIK DI JAWA TENGAH MENGGUNAKAN SMARTHPONE (Information Technology and Telematics, 2015)
Abstract--- Batik (or word Batik) derived from the Javanese "amba" means writing and nitik. Batik is the art of painting done on cloth using wax as a protector for decoration on the cloth. Moreover, since 2009 Batik Indonisia officially recognized as a UNESCO cultural heritage non-human objects. Batik as an element of culture has indeed been passed on from generation to generation up to the present generation. System development method used in this study is a prototype that consists of identifying the needs of the user, make a prototype, test the prototype, refine the prototype, developed a version of the product. System design using OOD which consists of the use case diagram mdan activity diagram sequence diagrams. Making the program using the Android programming. The end result of this research is the application of information-based Android Central Javanese batik can be used to display information consisting of the history of batik, batik and tools in the form of text and images can also display video batik and batik. Keywords--- Batik, OOD, Android, Prototype